Serum Levels of Lipoprotein(a) and Homocysteine in Patients on Hemodialysis Who Take Hydroxymethylglutaryl-CoA Reductase Inhibitors, Vitamin B6, and Folic Acid (Iranian Journal of Kidney Diseases, 2009)
Introduction. High serum levels of lipoprotein(a) and homocysteine are risk factors of cardiovascular disease which are prevalent in patients on hemodialysis. Controversy exists about the effects of hydroxymethylglutaryl-CoA reductase inhibitors on serum lipoprotein(a) levels in patients on hemodialysis. Also, deficiency of some water soluble vitamins and administration of statins may raise serum levels of homocysteine in these patients. This study was designed to investigate serum levels of lipoprotein(a) and homocysteine in patients on hemodialysis who were taking a statin, vitamin B6, and folic acid.Materials and Methods. We investigated on 152 patients with maintenance hemodialysis who were taking atorvastatin or lovastatin, vitamin B6, and folic acid for at least 6 months. Their serum levels were obtained to measure lipoprotein(a) and homocysteine levels, as well as triglyceride, total cholesterol, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol.Results. The mean serum values of total cholesterol, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol and triglyceride were significantly less than the maximum reference values (P < .001). The mean serum level of lipoprotein(a) was also less than the reference value (P = .009), but homocysteine level was 33% higher on average than the reference value (P < .001).Conclusions. Our study demonstrated that in our patients on hemodialysis, the mean serum level of homocysteine was about 30% higher than the reference value although they were receiving vitamin B6 and folic acid. Hence, they were still exposed to the risk of cardiovascular disease.